Effects of Teachers’ Moral Lesson Activities on Students’ Behaviors in Early Childhood Education Classrooms - Alam, Jan (JECCE, 2023)
Through the lens of Vygotsky zone of proximal development theory, the study aims to find the effects of teachers’ moral lesson activities on students’ behaviors in early childhood education classrooms. Based on the two major hypothesis, 1. There is a significant effect of teachers’ moral lesson activities on students’ behaviors and 2. There is a significant difference in teachers’ views in relation to their gender, age, qualification, and experience, the study adopted descriptive research design. Data for the study were collected via online survey forms from 320 early childhood education teachers via a self-developed questionnaire in the District of Charsadda, Khyber Pakhtunkhwa, Pakistan. The collected data were analyzed via SmartPLS4 to find structural and measurement models. There results indicated that there is a significant effect of teachers’ moral lesson activities on students’ behaviors and there is no significant difference in teachers’ views in relation to their gender, age, qualification, and experience.